2018
DOI: 10.1016/j.solener.2018.01.078
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage optimisation of hybrid solar power plants

Abstract: Hybrid solar power plants which combine concentrated solar power (CSP) and photovoltaic (PV) systems with thermal energy storage (TES) have the potential to provide cost competitive and dispatchable renewable energy. The integration of energy storage gives dispatchability to the variable renewable generation while the combination of different generation technologies can reduce the costs. However, the design of reliable and cost competitive hybrid solar power plants requires the careful balancing of trade-offs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…This means that all the new CSP capacity added to the system have a solar multiple of 2.5, power block efficiencies of 37% and 17.5 h of thermal storage capacity. These values also agree with the optimal values found by Bravo et al [32].…”
Section: Csp and Hydroelectric Reservoir Modellingsupporting
confidence: 92%
“…This means that all the new CSP capacity added to the system have a solar multiple of 2.5, power block efficiencies of 37% and 17.5 h of thermal storage capacity. These values also agree with the optimal values found by Bravo et al [32].…”
Section: Csp and Hydroelectric Reservoir Modellingsupporting
confidence: 92%
“…In order to handle both objectives, and according to the results presented in [24], here a linear scalarisation method is implemented. The model developed in [24], which optimises the annual operation of a hybrid solar power plant with energy storage, found that the linear scalarisation method works faster than the epsilon ( ) constrain method, obtaining the same Pareto frontier. The only precaution is to choose a suitable scaling factor (ω) to scale the second objective (section 3.3 presents the analysis to define the value of ω for the case study described below).…”
Section: Scalarisation Methodsmentioning
confidence: 99%
“…In the simplified model shows in figure 1, the power flows to the inverter and then is dispatched to the grid. According the model described in [24], the total efficiency of the PV plant, from the solar irradiation to the electric power, considers the efficiency of panels and inverters, in addition with the losses related with module mismatch, connections and wiring.…”
Section: Photovoltaic Power Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability of the solar irradiation in the Atacama Desert (northern Chile with a GHI of 3300 kWh/m 2 on latitude tilt surfaces [24]) is influenced by ENSO. These phenomena will result in years with significantly different solar irradiation than the TMY [25]. The solar radiation time series have characteristics associated with natural climatic phenomena, revealing that a reduction in solar radiation can be considered an indirect indicator of an ENSO period [26].…”
Section: Introductionmentioning
confidence: 99%